1999
DOI: 10.1097/00000478-199910000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Crypt Foci in the Human Colon

Abstract: Aberrant crypt foci are considered potential markers of colorectal cancer risk. The aim of this study was to analyze a large series of human aberrant crypt foci according to frequency, distribution, and histology. Aberrant crypt foci were identified in methylene blue-stained colonic mucosa from 103 patients undergoing surgery for colorectal cancer or diverticular disease. Foci were histologically classified into surface hyperplastic type, surface and glandular hyperplastic type, mixed hyperplastic and adenomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The incidences of dysplastic ACF, which are crucial from the carcinogenesis point of view, reported in various studies differ. The lowest percentages of dysplastic ACF were presented by Nascimbeni, Adler, and Rudolph; those reported by Takayama are comparable to our findings [ 8 , 11 , 15 , 22 ]. There are also studies in which the percentages in question are higher than those observed in our population.…”
Section: Discussionsupporting
confidence: 90%
“…The incidences of dysplastic ACF, which are crucial from the carcinogenesis point of view, reported in various studies differ. The lowest percentages of dysplastic ACF were presented by Nascimbeni, Adler, and Rudolph; those reported by Takayama are comparable to our findings [ 8 , 11 , 15 , 22 ]. There are also studies in which the percentages in question are higher than those observed in our population.…”
Section: Discussionsupporting
confidence: 90%
“…With the advent of new molecular biology assays, further characterization of ACF genetic profiles to assess their risks of progression to cancers are possible [ 44 ]. These categories consist of epigenetic silencing, genetic mutation, microsatellite instability and loss of heterozygosity ( Table 2 ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Epigenetic silencing of genes involved in cancers has been an area of intense research over the last decade [ 63 ].…”
Section: Acf As a Relevant Biomarker For Colon Cancer: Molecular Amentioning
confidence: 99%
“…Other studies have reported similar incidence rates of ACF in these age brackets (15,16). It is essential to identify and remove these early lesions for an adequate CRC prevention strategy (17). Furthermore, accurate tumor grading is necessary for patient survival and can be achieved most effectively in stained histopathological sections harvested via biopsy or during surgery.…”
Section: Introductionmentioning
confidence: 99%